Single-Dose CpG Immunization Protects Against a Heterosubtypic Challenge and Generates Antigen-Specific Memory T Cells - Vogel, Alexander J.; Brown, Deborah M. (Frontiers in Immunology, 2015)
Despite extensive research, influenza A virus (IAV) remains a major cause of morbidity, mortality, and healthcare expenditure. Emerging pandemics from highly pathogenic IAV strains, such as H5N1 and pandemic H1N1, highlight the need for universal, cross-protective vaccines. Current vaccine formulations generate strain-specific neutralizing antibodies primarily against the outer coat proteins, hemagglutinin and neuraminidase. In contrast to these highly mutable proteins, internal proteins of IAV are more conserved and are a favorable target for developing vaccines that induce strong T cell responses in addition to humoral immunity. Here, we found that intranasal administration with a single dose of CpG and inactivated x31 (H3N2) reduced viral titers and partially protected mice from a heterosubtypic challenge with a lethal dose of PR8 (H1N1). Early after immunization, vaccinated mice showed increased innate immune activation with high levels of MHCII and CD86 expression on dendritic cells in both draining lymph nodes and lungs. Three days after immunization, CD4 and CD8 cells in the lung upregulated CD69, suggesting that activated lymphocytes are present at the site of vaccine administration. The ensuing effector Th1 responses were capable of producing multiple cytokines and were present at least 30 days after immunization. Furthermore, functional memory responses were observed, as antigen-specific IFN-γ+ and GrB+ cells were detected early after lethal infection. Together, this work provides evidence for using pattern recognition receptor agonists as a mucosal vaccine platform for inducing robust T cell responses capable of protecting against heterologous IAV challenges.